Development of epicuticular wax and cuticular ornamentation in Hevea brasiliensis (Willd. ex. Adr.de Juss.) Muell. Arg. - Premakumari D; Panikkar A O N; Sethuraj M R (Indian Journal of Natural Rubber Research, 1989)
The general pattern and phenology of epicuticular wax in Hevea brailiensis (Willd. ex Adr. de Juss.) Muell. Arg. was studied with the aid of scanning electron microscope. The developmental stages of wax formation in relation to the phenology of leaf in Hevea and general pattern of epicuticular wax on the leaf surface, petiole, petiolule, tender stem and fruit wall have been described. Functional importance and possible utility of the wax pattern in disease management and clone identification in Hevea have been discussed. The role of epidermal structure on organographic specificity to Phytophthora leaf fall disease in Hevea has been confirmed on the basis of wax pattern.
Keywords: Cuticular ornamentation; Cuticular ornamentation; Epicuticular wax; Epicuticular wax; Epidermis; Epidermis; Hevea brasiliensis; Hevea brasiliensis